2012
DOI: 10.1007/s12028-012-9684-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Serum Brain Natriuretic Peptide and Cardiac Troponin in Elective Intracranial Surgery

Abstract: An intracranial mass effect is associated with higher NT-proBNP serum levels in patients with a brain neoplasm. Following elective intracranial surgery for brain tumor resection NT-proBNP values increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Studies in traumatic brain injury patients found that more severe brain damage was associated with greater elevation of NT-proBNP concentrations in serum and in cerebrospinal fluid 7 , 27 . In a similar vein, greater mass effect and perifocal edema is associated with higher serum NT-proBNP concentrations in primary and metastatic brain tumor patients 13 , 14 . Necrosis and peri-tumoral edema are characteristics of rapidly growing aggressive brain tumors, and therefore can contribute to the observed increase of serum NT-proBNP concentrations.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies in traumatic brain injury patients found that more severe brain damage was associated with greater elevation of NT-proBNP concentrations in serum and in cerebrospinal fluid 7 , 27 . In a similar vein, greater mass effect and perifocal edema is associated with higher serum NT-proBNP concentrations in primary and metastatic brain tumor patients 13 , 14 . Necrosis and peri-tumoral edema are characteristics of rapidly growing aggressive brain tumors, and therefore can contribute to the observed increase of serum NT-proBNP concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…Tumor grade, patient age and functional status, and extent of surgical tumor resection are the most important prognostic indicators for malignant brain tumors 12 . Two previous studies in primary and metastatic brain tumor patients reported that greater NT-proBNP concentration was associated with greater mass effect and extent of perifocal brain edema 13 , 14 . However, the association of NT-proBNP concentration with health status and prognosis of brain tumor patients was not reported.…”
Section: Introductionmentioning
confidence: 95%
“…In line with previous findings, we found that cardiovascular comorbidity and older age were related to greater NT-proBNP concentrations [25,26], suggesting that NT-proBNP can be a valuable biomarker of underlying cardiovascular function impairment of BT patients. However, Ruggieri et al [18] in a sample of 108 BT patients found no association between increase in NT-proBNP and cardiac dysfunction; levels of NT-proBNP were directly associated with cerebral damage. Clinical importance of subclinical impairment of cardiac function as well as its clinical biomarkers warrants further research in BT patient population despite our preliminary negative results.…”
Section: Discussionmentioning
confidence: 92%
“…Inflammatory response is important for development, progression, and prognosis of malignant [15,16] and benign [17,18] BTs. Greater circulating hsCRP concentration was linked to shorter survival of glioma [19] and meningioma [20] patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ruggieri et al [20] analyzed N-terminal pro-brain natriuretic peptide and the prognostic value of serum cardiac troponin T in patients with no history of cardiac anomalies before and after elective surgery for intracranial tumor resection. Serum troponin T and N-terminal pro-brain natriuretic peptide levels were measured in 108 patients.…”
Section: Discussionmentioning
confidence: 99%